2019
DOI: 10.1002/suco.201900128
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of RC flat slabs with shear bolts under reversed horizontal cyclic loading

Abstract: An experimental work on reinforced concrete flat slab specimens to test the efficiency of postinstalled bolts, as punching shear reinforcement in resisting vertical and cyclic horizontal loads, was conducted and is presented in this paper. The test protocol consisted in increasing horizontal drifts combined with constant vertical load until failure. Two different detailing solutions for the shear reinforcement were considered, one using a radial distribution around the column and another using a cross distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Almeida et al 28 , 17 tested four specimens reinforced with stirrups around the column. Two shear reinforcement ratios were tested: one was achieved by using 16 vertical legs of diameter 4.5 mm per perimeter and a higher ratio was achieved by using eight legs of diameter 6 mm plus eight legs of diameter 8 mm.…”
Section: Punching Shear Capacity Enhancement Methods Investigatedmentioning
confidence: 99%
See 3 more Smart Citations
“…Almeida et al 28 , 17 tested four specimens reinforced with stirrups around the column. Two shear reinforcement ratios were tested: one was achieved by using 16 vertical legs of diameter 4.5 mm per perimeter and a higher ratio was achieved by using eight legs of diameter 6 mm plus eight legs of diameter 8 mm.…”
Section: Punching Shear Capacity Enhancement Methods Investigatedmentioning
confidence: 99%
“…Almeida et al 17,28 tested two specimens strengthened with post‐installed bolts in two arrangements: radial and cruciform. Three perimeters of 12 M10 bolts were used, with a shear reinforcement area per layer similar to the specimens with studs.…”
Section: Punching Shear Capacity Enhancement Methods Investigatedmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The Lisbon setup represents an attempt to comply with the actual boundary conditions of a continuous flat slab. In the last years, several researchers used it: Isufi et al 24 investigated the use of rail studs, Almeida et al showed the influence of closed steel stirrups 25 and the use of postinstalled shear bolts, 26 while Gouveia et al 27 investigated the response of SFRC flat slabs. The numerical model of a theoretical continuous setup is also developed, using the same mechanical parameters of Almeida's specimens.…”
mentioning
confidence: 99%